Post-operative management of flexor tendon injuries at zone II and flexor pollicis longus – a survey of Irish practice. Issue 2 (18th October 2021) - Spirtos, Michelle; Naughton, Mary; Carr, Emma; Stapleton, Tadhg; O'Donnell, Michelle
Abstract : Purpose: The post-operative management of flexor tendon injuries has been the focus of considerable exploration and there continues to be variation in approaches and methods of mobilisation. The purpose of this paper is to explore therapy management following repair to flexor tendons at zone II and flexor pollicis longus (FPL) (all zones) in Ireland. Design/methodology/approach: A descriptive survey questionnaire design through an online format was used. Therapists were recruited through the Irish Association of Hand Therapists, the national bodies for occupational therapy and physiotherapy, and therapy managers in acute hospitals, with 29 therapists participating in the study. Descriptive statistics were used to analyse the survey data. Findings: Patients were generally seen three to five days following surgery. Early active mobilisation approaches were favoured by all but one therapist, with 62% using the Belfast protocol and 34% the Manchester Short Splint (MSS) protocol. Each early active protocol exercise session commences with passive motion followed by graded active flexion. Tenodesis is incorporated by the majority of respondents within the first four weeks. Therapy programme and splints are modified based on patient presentation. Resistance exercises are commenced from week seven. Patient compliance was identified as the most influential factor in the post-operative intervention approach taken. Originality/value: This study provides the first Irish profile of current practice in the post-operative management of flexor tendon repairs at zone II and FPL which has not previously been reported. Further research should explore the reasoning behind the interventions chosen and also the implications for practice of changes to surgical techniques.